Estudio y optimización de la variabilidad y sus efectos en un OTA con degeneración de cuerpo - Molina-Robles, Roberto Carlos (Instituto Tecnológico de Costa Rica, 2016)
In this report, it is documented a study about transistors mismatching in Operational Transconductance Amplifiers (OTA), particularly a body degenerated OTA. With the help of Dr. Alfredo Arnaud, Dr. Roberto Pereira and Dr. Alfonso Chacón, the analysis over this specific OTA was established as a starting point. During the project, a theoretical study was made, the resulting simulation model was implemented and incorporated in an optimization process developed at the Electronics Engineering School. Then, several study points were chosen and analyzed from the simulation results, this way, the effect of the transistors mismatch produced over the rest of parameters could be studied. At the end, the results of the study points’ simulations were validated with post-layout simulations. In the present document, you will find all related information about the developed project: theoretical fundaments, design, tests, optimization, analysis results, etc.
Proyecto de Graduación (Maestría en Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2016.
Keywords: Algoritmos; Amplificadores; Probabilidad; Simulaciones; Ingeniería en electrónica